Atividade enzimática em lodo de esgoto contaminado com cádmio e uso em solo cultivado com sorgo - Frade Junior, Elizio Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O conhecimento de atributos bioquímicos dos resíduos, associado à disponibilidade de metais pesados em virtude da utilização de lodo de esgoto em solos agricultáveis, tem por objetivo fornecer ferramentas para minimizar os riscos de poluições ambientais trazidos pela utilização do lodo de esgoto nos solos. Portanto, para avaliar o efeito do nível de contaminação de cádmio nas propriedades bioquímicas do lodo de esgoto e posterior disponibilidade do metal no solo, foram incubadas amostras de 500g de lodo com CdCl2, CdSO4, Cd(NO3)2 e Cd metálico em casa de vegetação. Posteriormente, lodo incubado e não incubado, na dose de 10 Mg ha-1, foram adicionados a amostras de Latossolo Vermelho distrófico e cultivado com sorgo granífero. Determinaram-se as atividades enzimáticas de amilases, arilsulfatases, desidrogenases e proteases nas amostras de lodo incubadas durante 58 dias. Após incubação e cultivo de sorgo granífero com lodo incubado e não incubado, avaliaram-se os teores de cádmio extraídos com Mehlich I e DTPA no lodo incubado e a disponibilidade do metal em amostras de terra, coletadas aos 60 e 120 dias de cultivo, com os extratores DTPA, HNO3 e HF. As fontes de cádmio adicionadas ao LE alteraram a atividade enzimática de amilases, arilsulfatases, desidrogenases e proteases. A produção de matéria seca e grãos pela cultura do sorgo granífero não foram influenciadas pelos tratamentos no lodo, assim como, pelas fontes acrescidas de cádmio. A extração de cádmio do solo foi influenciada pelo período de incubação.

Knowing the biochemical attributes of residues, associated with the heavy metals availability due to the use of sewage sludge in cropped soils, aims to supply tools in order to minimize the risks of environmental pollution brought by the use of that residue as a fertilizer. However, in order to evaluate the effect of the contamination level by the addition of cadmium on the biochemical properties of the sewage sludge and the posterior metal availability in the soil, 500g of sludge were incubated with CdCl2, CdSO4, Cd(NO3) or metallic Cd in a green house. Incubated and no-incubated sewage sludge was then added to a Typic Haplorthox in the rate 10 mg/ha and sorghum was grown. Enzymatic activity of amylases, arylsulphatases, dehydrogenases and proteases in the sewage sludge samples incubated for 58 days were evaluated. Cadmium was evaluated in the sewage sludge incubated for 58 days using the extractors Mehlich I and DTPA and in soil samples obtained at the 60th and 120th days of sorghum cultivation using the extractors DTPA, HNO3 and HF. The results demonstrated that the time of incubation, as well as the cadmium sources, clearly influenced sewage sludge enzymatic activities by increasing and decreasing the activities. Cadmium sources did not alter significantly the amounts of metal extracted from incubated sewage sludge with Mehlich I and DTPA extractors. Cadmium extraction from soil samples treated with sewage sludge incubated with Cd was greater with DTPA and HNO3 extractors. The different Cd sources added to sewage sludge affected the activity of amylases, arylsulphatases, dehydrogenases and proteases in the residue. Dry matter and grain production by sorghum were not affected by the treatments apppied to sewage sludge (incubation and no-incubation) and by the Cd sources. Cd extracted from the soil was affected by the incubation of sewage sludge after Cd contamination.
Keywords: biosolids; biochemistry; Sludge enzyme; Extractors; Heavy metals; Residues; Bioquímica; Metais pesados; Resíduo; Biossólido; Enzimas de lodo; Extratores